1985
DOI: 10.1620/tjem.147.267
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood group antigens of human spermatozoa.

Abstract: ABO blood group antigens on the membrane of human spermatozoa were investigated with the peroxidase-labelled antibody test. Spermatozoa from 0 secretor were incubated with saliva or seminal plasma of A and B secretors, but the specific peroxidase staining was negative. This result indicates that blood group antigens on human spermatozoa originate from spermatozoon itself, but not from seminal plasma. ABO blood group antigens ; human spermatozoa ; peroxidase-labelled antibody test Yamakami (1926) reported that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is basically accepted that ABH antigens can be detected on the spermatozoa extracted from seminal stains, However, it has long been a controversial subject whether the ABH antigens on the spermatozoa are inherent to the membrane or coating antigens. Takeda and Hiraiwa (1985) also reported that the adherence of A or B antigens from saliva or seminal fluid to O type spermatozoa was not observed after incubation in appropriate saliva or seminal fluid and the ABH antigens recognized on spermatozoa are inherent antigens of the sperm. Takeda and Hiraiwa (1985) also reported that the adherence of A or B antigens from saliva or seminal fluid to O type spermatozoa was not observed after incubation in appropriate saliva or seminal fluid and the ABH antigens recognized on spermatozoa are inherent antigens of the sperm.…”
Section: Discussionmentioning
confidence: 99%
“…It is basically accepted that ABH antigens can be detected on the spermatozoa extracted from seminal stains, However, it has long been a controversial subject whether the ABH antigens on the spermatozoa are inherent to the membrane or coating antigens. Takeda and Hiraiwa (1985) also reported that the adherence of A or B antigens from saliva or seminal fluid to O type spermatozoa was not observed after incubation in appropriate saliva or seminal fluid and the ABH antigens recognized on spermatozoa are inherent antigens of the sperm. Takeda and Hiraiwa (1985) also reported that the adherence of A or B antigens from saliva or seminal fluid to O type spermatozoa was not observed after incubation in appropriate saliva or seminal fluid and the ABH antigens recognized on spermatozoa are inherent antigens of the sperm.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we tried to isolate sperm mixtures from multiple donors with different ABO blood group antigens. As ABO blood group antigens are located on sperm surface2425 and would facilitate the success of flow cytometry based sperm separation, therefore, it is imperative that we should first determine whether the genotype of semen is a secretor or non-secretor, followed by FACS separation to isolate type O, A, B, or AB sperm using ABO blood group antigen antibodies. It is known that the frequency of secretors: non-secretors is approximately 1:4, in spite of a slightly variation for different ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…Antigens specific only to spermatozoa and the seminal plasma as well as antigens common to the spermatozoa and other kinds of human cells have been identified and localized on human spermatozoa (Takeda & Hirava, 1985;Anderson et al, Correspondence: Associate Professor Dr Ts. Ts.…”
Section: Introductionmentioning
confidence: 99%